2002
DOI: 10.1002/hbm.10064
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine and fMRI BOLD signal: Distinguishing between effects mediated by change in blood flow versus change in cognitive state

Abstract: No human fMRI studies have examined ketamine effects on the BOLD signal change associated with cognitive task performance. We wished to distinguish between effects on 1) cerebral blood flow, with resultant change in BOLD signal; and 2) cognition and neural mechanisms underlying BOLD signal change associated with task performance. Eight right-handed men (mean age 28.75 years) received ketamine or saline i.v. in a randomized, double-blind manner (bolus 0.23 mg/kg; 0.5 mg/kg over 45 min to a maximum 1 hr). Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…Interestingly, the functional response appeared 2-3 s later than that using alpha-chloralose. The amplitude of the response was also slightly decreased, as already observed in human (Abel et al, 2003).…”
Section: Anaestheticsupporting
confidence: 66%
“…Interestingly, the functional response appeared 2-3 s later than that using alpha-chloralose. The amplitude of the response was also slightly decreased, as already observed in human (Abel et al, 2003).…”
Section: Anaestheticsupporting
confidence: 66%
“…First, we cannot fully exclude the possibility that our imaging findings were associated with an unspecific effect of S-ketamine on cerebral blood flow. However, recent studies suggest that ketamine administration rather results in an altered BOLD response specific to the cognitive task (Northoff et al 2005) or the emotional stimuli (Abel et al 2003) presented than in a nonspecific global effect on cerebral blood flow per se. Further support for this argument comes from animal studies, which also suggest that ketamine has no effects on vascular mechanisms beyond its specific effects on neural activation (Burdett et al 1995).…”
Section: Discussionmentioning
confidence: 98%
“…The consequences of ketamine and placebo and their effects on BOLD versus alterations in cognitive state in healthy participants has also been examined. 43 The changes in BOLD signal during perception of the face-nonface contrast exhibited widespread BOLD changes. However, in the placebo group compared with in the ketamine group, there was significantly greater BOLD signal change only in the middle occipital gyrus (BA 18) and the precentral gyrus (BA 4).…”
Section: Direct Effects Of Psychotropic Medications On Cbf In Healthymentioning
confidence: 99%
“…The authors suggested that the BOLD signal changes represented task-dependent effects of drug or placebo, rather than taskindependent effects of drug. 43 The effects of lamotrigine on BOLD signal changes induced by transcranial magnetic stimulation (TMS) have also been examined in healthy participants. 44 Lamotrigine at clinically relevant serum concentrations diffusely inhibited cortical activation induced by TMS applied over the motor cortex.…”
Section: Direct Effects Of Psychotropic Medications On Cbf In Healthymentioning
confidence: 99%